2004
DOI: 10.1523/jneurosci.0292-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Central Nucleus of the Amygdala in Mediating Fear and Anxiety in the Primate

Abstract: Numerous studies demonstrate that the rhesus monkey is an excellent species with which to investigate mechanisms underlying human emotion and psychopathology. To examine the role of the central nucleus of the amygdala (CeA) in mediating the behavioral and physiological responses associated with fear and anxiety, we used rhesus monkeys to assess the effects of excitotoxic lesions of the CeA. Behavioral and physiological responses of nine monkeys with bilateral CeA destruction (ranging from 46 to 98%) were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
324
5
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(367 citation statements)
references
References 49 publications
36
324
5
2
Order By: Relevance
“…We believe this evidence suggests that heightened affiliative social interactions following amygdala lesions stems from a more general inability to properly perceive danger or threat in the environment and use such information to modulate social behavior adaptively. In line with this view, deficits in threat detection or fear reactivity have been specifically demonstrated for monkeys with bilateral neurotoxic amygdala lesions in both social (Machado & Bachevalier, 2006) and nonsocial settings (Izquierdo, Suda, & Murray, 2005;Kalin, Shelton, & Davidson, 2004;Kalin, Shelton, Davidson, & Kelley, 2001;Mason et al, 2006;Meunier, Bachevalier, Murray, Málková, & Mishkin, 1999). These abnormalities are not restricted to nonhuman primates, since humans with amygdala lesions also demonstrate specific deficits in identifying fearful facial expressions (Adolphs et al, 1999), rating the magnitude of fearful expressions (Adolphs, Tranel, Damasio, & Damasio, 1995) and assessing the approachability or trustworthiness of unfamiliar individuals (Adolphs, Tranel, & Damasio, 1998).…”
Section: Social Disinhibition Persists Across Contextsmentioning
confidence: 80%
“…We believe this evidence suggests that heightened affiliative social interactions following amygdala lesions stems from a more general inability to properly perceive danger or threat in the environment and use such information to modulate social behavior adaptively. In line with this view, deficits in threat detection or fear reactivity have been specifically demonstrated for monkeys with bilateral neurotoxic amygdala lesions in both social (Machado & Bachevalier, 2006) and nonsocial settings (Izquierdo, Suda, & Murray, 2005;Kalin, Shelton, & Davidson, 2004;Kalin, Shelton, Davidson, & Kelley, 2001;Mason et al, 2006;Meunier, Bachevalier, Murray, Málková, & Mishkin, 1999). These abnormalities are not restricted to nonhuman primates, since humans with amygdala lesions also demonstrate specific deficits in identifying fearful facial expressions (Adolphs et al, 1999), rating the magnitude of fearful expressions (Adolphs, Tranel, Damasio, & Damasio, 1995) and assessing the approachability or trustworthiness of unfamiliar individuals (Adolphs, Tranel, & Damasio, 1998).…”
Section: Social Disinhibition Persists Across Contextsmentioning
confidence: 80%
“…Since the amygdala mediates adaptive and maladaptive fear and anxiety responses (Blanchard and Blanchard, 1972;LeDoux, 2000;Davis and Whalen, 2001;Amaral, 2003;Kalin et al, 2004), it is of particular importance that ferret exposure increased c-fos expression within various nuclei of the amygdala. Consistent with previous studies using cat odor as a stimulus (Dielenberg et al, 2001;McGregor et al, 2004) we found that 10 min of ferret exposure resulted in a robust increase in the number of Fos-positive cells within the MeA.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence implicates the amygdala in conditioned and unconditioned fear responses (Blanchard and Blanchard, 1972;LeDoux, 2000;Davis and Whalen, 2001;Amaral, 2003;Kalin et al, 2004), and human functional imaging studies have demonstrated increased amygdala activation in some patients with anxiety and depressive disorders (Drevets, 2003;Rauch et al, 2003). Furthermore, evidence supports a role for the amygdala CRF system in mediating anxiety and fear.…”
Section: Introductionmentioning
confidence: 99%
“…The Ce is of interest because its efferent projections coordinate autonomic, hormonal, behavioral, and emotional responses to stress (20), and Ce lesions in monkeys are sufficient to reduce AT (21). Furthermore, rodent studies demonstrate that direct Ce manipulations markedly alter unconditioned anxiety responses (22), similar to those elicited by novel or potentially threatening situations in children with high AT.…”
mentioning
confidence: 99%